Fenomena Toxic Relationship dalam Berpacaran - Putra, Driyadha Adhe; Purbaning, Prias Hayu (SOLUTION, 2023)
The aims of this study were to: 1) Find out how high the phenomenon of toxic relationships is in dating among students of the 2020-2021 batch of the Guidance and Counseling Study Program, Sanata Dharma University. 2) Knowing the dominant forms of toxic relationships experienced by Guidance and Counseling students at Sanata Dharma University. 3) Knowing the efforts made to escape from a toxic relationship. This research uses quantitative descriptive analysis. The subjects in the research were 105 students of the Guidance and Counseling Study Program at Sanata Dharma University, class of 2020-2021. This study uses a toxic relationship scale instrument with a total of 32 items. There are 28 valid items and have a Cronbach Alpha reliability index 0,934. The results of this study indicate that 1) 7.55% or 8 students experience a toxic relationship in the very high category. 2) 10.36% or 11 students experience toxic relationships in the high category. 3) 16.04% or 17 students are in the medium category. 4) 12.26% or 13 students show the level of toxic relationship is in the low category. 5) 53.77% or 56 students show a very low toxic relationship phenomenon. The highest forms of toxic relationships experienced by students were in the psychological aspect with a total of 40 students (38.1%) and 13 students (12.4%). Most students acquire the ability to consider solutions with a total of 91 students (86.7%) and 80 students (76.2%).